PENGARUH KLAIM REOG PONOROGO OLEH MALAYSIA TERHADAP HUBUNGAN BILATERAL INDONESIA-MALAYSIA - Satrio Suryo Negoro; Christy Damayati, GPH. Dipokokusumo (Solidaritas, 2017)
PENGARUH KLAIM REOG PONOROGO OLEH MALAYSIA TERHADAP HUBUNGAN BILATERAL INDONESIA-MALAYSIA Satrio Suryo NegoroDra. Chirsty Damayati, M.siDrs. GPH. Dipokokusumo, M.siThis thesis discusses the effect of Malaysia’s claims for Reog Ponorogo on Indonesia-Malaysia bilateral relation. National culture gives a nation the typical characteristic; Reog Ponorogo is a dancing cultural art belonging to Indonesia. Reog is a national culture and soft power that can be used by Indonesia to affect other countries; therefore Indonesia defends soft power it has verily. Indonesia as a national power and herewith Indonesia emphasizes on soft power as it is a very useful power to cooperate with other countries. Because Reog Ponorogo is very attractive, it makes Malaysia claim it as their culture. In this case, the research employed national cultural theory, national and bilateral relationship. And the method employed was qualitative method by collecting primary and secondary data from books, journal and literature, and interview. In this presence of cultural claim, Indonesian government initiated to register the cultures it has to UNNESCO in order to be recognized by other countries. In this case, the claim for Indonesian culture by Malaysia affected Indonesia-Malaysia bilateral relation in which both of them had established much cooperation in many sectors; this case impacted on, among others: mistreatment against Indonesian workers in Malaysia, inhibited investment of both countries leading to the decreased economic income, decreased number of Indonesian workers going to Malaysia annually, reduced number of student exchanges between countries and no cooperation between students studying in Malaysia an those studying in Indonesia. That was due to cultural claim made by Malaysia. Keywords: Bilateral Relations, Soft Power, Reog Ponorogo, Malaysia’s claim, cultural heritage.